A game of Noctis - Fagan, Deva (Atheneum Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2024)
A thrilling middle grade fantasy about a girl who must participate in a deadly game with a ragtag team of players to save her grandfather from a terrible fate--perfect for fans of James Riley and Shannon Messenger! In the opulent, sinking city of Dantessa, the Great Game rules all. Pia Paro believes that so long as you follow the rules, you always have a chance at winning. But after her beloved Gramps is sentenced to a life of servitude, Pia accepts a dangerous offer and joins a team of players seeking to win the most perilous game of all: Noctis. The Seafoxes--Pia's new teammates--are unlike anyone she's ever met. There's brash, bold Carlo; macabre Serafina; kindhearted Pasquale; and their dashing ringleader, Vittoria. Each has their own reason for playing, and soon, Pia begins to question all her long-held beliefs. Maybe the rules Pia once trusted to lift her up have only been keeping her--and thousands of others like her--down. As she struggles with these revelations, Pia must survive a gauntlet of clockwork soldiers, perilous underwater adventures, and even a game against Death herself. But with Pia's grandfather's life at stake, Pia must finally decide whether she's brave enough to not just break the rules, but to change the very nature of the Game.